Integrating Aboriginal cultural values into water planning: a case study from New South Wales, Australia. Issue 3 (3rd July 2019) - Moggridge, Bradley J.; Betterridge, Lyndal; Thompson, Ross M.
ABSTRACT: Australia is the driest inhabited continent on Earth and has an acute need to manage its water resources effectively. Australian Aboriginal peoples have a profound knowledge of surface water and groundwater which has allowed them to thrive for thousands of generations even in the most arid parts of the landscape. Aboriginal peoples place a high priority on protecting water, but the challenge is to ensure that their values are integrated into water planning. The Australian New South Wales (NSW) government's Aboriginal Water Initiative (AWI) (2012-2017) sought to include Aboriginal cultural and spiritual values in water management. The AWI operated under the NSW Government's Water Management Act 2000, which seeks to protect the cultural and spiritual values of water and the benefits to flow to Aboriginal peoples. Speaking from the perspective of the previous leader of the AWI, this article will reflect on its inception and structure, particularly focussing on approaches of engagement and consultation. These were highly structured and included a focus on cultural training and protocols and benefited from having Aboriginal staff involved. While ultimately discontinued in 2017, a reflection on the AWI provides useful insights into how engagement and consultation can be operationalised in water management and policy.